Application of targeted metabolomics to reveal associations between carbohydrate quality and cardiometabolic risk factors - Guirette, Mélanie. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Nutrition Epidemiology and Data Science.; Advisor: Nicola McKeown.; Committee: Mark Herman, Danielle Haslam, and Jiantao Ma.; Keyword: Epidemiology.